Engaging students with archival and digital resources - Cotton, Justine; Sharron, David (Witney : Chandos, 2011)
Aimed at professional librarians and archivists, this book explores how to connect students and faculty with the archival and digital collections of their university's library. Key sections include: how to look at archives in a digital world; reaching out to faculty to get them to use archival and digital resources; working with students and how to best deliver instruction; creating lessons and assignments; assessment how to gauge your successes and learn from your failures. This book provides librarians and archivists with the robust tools they need to develop a comprehensive workshop program aimed at connecting students with archival and digital collections
Includes bibliographical references and index.
oif 20/06/14
Loan
Keywords: Archival resources -- Study and teaching (Higher) .; Electronic information resources -- Study and teaching .